Pricing Currency Risks - CHERNOV, MIKHAIL; DAHLQUIST, MAGNUS; LOCHSTOER, LARS (Journal of Finance, 2023)
ABSTRACT The currency market features a small cross‐section, and conditional expected returns can be characterized by few signals: interest differential, trend, and mean reversion. We exploit these properties to construct the ex ante mean‐variance efficient portfolio of individual currencies. The portfolio is updated in real time and prices all prominent currency trading strategies, conditionally and unconditionally. The fraction of risk in these assets that does not affect their risk premiums is at least 85%. Extant explanations of carry strategies based on intermediary capital or global volatility are related to these unpriced components, while consumption growth is related to the priced component of returns.